2019
DOI: 10.1093/ajcn/nqy265
|View full text |Cite
|
Sign up to set email alerts
|

Protein-quality evaluation of complementary foods in Indian children

Abstract: Background The types of food in complementary feeding of infants and young children are important for growth and development. Food protein quality, as measured by the Digestible Indispensable Amino Acid Score (DIAAS), requires the determination of true ileal digestibility of indispensable amino acids (IAAs) in children. Objectives First, the aim of this study was to measure the true ileal IAA digestibility of 4 (rice, finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…Tibambuya BA et al [31] also found that consumption of egg three or more times in a week could independently reduce the odds of anemia in pregnant women. Egg and cow's milk are ubiquitous globally and are known as top contributors for all nutrients as well as an exceptional protein source with a large range of micronutrients [32][33][34][35][36], and more importantly, egg is a fairly good source of iron [37] and milk is a good source of protein. Eggs and milk were widely used in previous nutritional intervention programs, such as the Lulin project [34], a randomized controlled trial conducted among young undernourished children in the Ecuadorian Andes, which showed dramatic effects on growth and stunting reduction via consuming eggs for just six months.…”
Section: Discussionmentioning
confidence: 99%
“…Tibambuya BA et al [31] also found that consumption of egg three or more times in a week could independently reduce the odds of anemia in pregnant women. Egg and cow's milk are ubiquitous globally and are known as top contributors for all nutrients as well as an exceptional protein source with a large range of micronutrients [32][33][34][35][36], and more importantly, egg is a fairly good source of iron [37] and milk is a good source of protein. Eggs and milk were widely used in previous nutritional intervention programs, such as the Lulin project [34], a randomized controlled trial conducted among young undernourished children in the Ecuadorian Andes, which showed dramatic effects on growth and stunting reduction via consuming eggs for just six months.…”
Section: Discussionmentioning
confidence: 99%
“…The low intake of high-quality protein intake, as well as amino acid, is associated with poor childhood growth [ 9 , 10 , 11 , 12 , 13 , 14 ]. In a targeted metabolomics approach, Semba and colleagues [ 11 ] showed that 16 of 19 measured proteinogenic amino acids were significantly associated with stunting in Malawian children.…”
Section: Discussionmentioning
confidence: 99%
“…The low intake of high-quality protein intake, as well as amino acid, is associated with poor childhood growth [ 9 , 10 , 11 , 12 , 13 , 14 ]. We did not include dietary intake in this analysis, and thus, we cannot exclude that tCys concentrations were only a marker of the overall quality of the diet and the role of other dietary components remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations